2010
DOI: 10.1016/j.vph.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary allergic reactions impair systemic vascular relaxation in ragweed sensitive mice

Abstract: Asthma is often associated with cardiovascular complications, and recent observations in animal models indicate that induction of pulmonary allergic inflammation increases susceptibility of the myocardium to ischemia and reperfusion injury. In this study, we used a murine model of allergen sensitization in which aspiration of allergen induces pulmonary and systemic inflammation, to test the hypothesis that pulmonary exposure to allergen alters vascular relaxation responses. BALB/C mice were sensitized by intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…This difference was not observed in vivo, with both groups showing similar low degree of collapse. Pulmonary arteries of asthmatic horses may show hypercontractility and impaired post-mortem relaxation similarly to what was previously demonstrated in experimental animal models of lung allergic inflammation [37][38][39]. However, differences in wall area (expression of wall thickening) were not affected by reactivity differences between groups and were similarly detected both in vivo and post-mortem, suggesting consistent remodeling of pulmonary artery walls in asthmatic horses.…”
Section: Plos Onesupporting
confidence: 79%
“…This difference was not observed in vivo, with both groups showing similar low degree of collapse. Pulmonary arteries of asthmatic horses may show hypercontractility and impaired post-mortem relaxation similarly to what was previously demonstrated in experimental animal models of lung allergic inflammation [37][38][39]. However, differences in wall area (expression of wall thickening) were not affected by reactivity differences between groups and were similarly detected both in vivo and post-mortem, suggesting consistent remodeling of pulmonary artery walls in asthmatic horses.…”
Section: Plos Onesupporting
confidence: 79%
“…We also recognize the potential importance of lipid oxidation that may occur and the close to ties to the oxidant/antioxidant balance that was not examined in this study but likely underlie the reports of oxidative stress following exposure. Our findings may support an alternative hypothesis for the general effect of a pulmonary exposure to EM, one in which the EM may not directly induce an significant initial inflammatory response but exacerbate an inflammatory response to a secondary insult, such as been described following inoculation with lipopolysaccharide (LPS) [ 52 ] or immune sensitization in asthma models associated with both vascular dysfunction and expansion of myocardial infarction [ 53 ]. Previous studies investigating the EMN exposure and pulmonary fibrosis in rats demonstrated that exposure to nanomaterials alone were insufficient to induce fibrosis.…”
Section: Discussionsupporting
confidence: 63%
“…Most previous studies investigating cardiovascular risk in asthma have been observational. In this study, we attempted to provide the physiological link between asthma and elevated cardiovascular risk [ 2 4 ], and to confirm experimental work demonstrating that pulmonary inflammation leads to systemic inflammation conducted in animal models [ 14 , 15 ] in a clinical laboratory setting. Previous work observed small but statistically significant changes in systemic levels of CRP and IL-6 when exposing otherwise healthy people to a pro-inflammatory insult, which resulted in both elevated arterial stiffness [ 17 ] and impairments in endothelial function [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from animal studies suggest that increased levels of systemic inflammation during asthma-like events originate in the lungs [ 14 , 15 ]. Indeed, markers of acute inflammation, such as C-reactive protein (CRP), are elevated in exhaled breath condensate during naturally occurring asthma exacerbations, and are correlated with CRP levels measured systematically at the same time-points [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%